Energy Efficient and robust routing with RPAR Protocol in Ad Hoc Networks - Reginald Pullagura, Joshua; Venkata Rao, D (International Journal of Engineering and Technology, 2017)
In ad hoc network, the topology of network changes frequently due to the mobile nature of nodes where the communication is possible without any fixed network infrastructure. Mobile nodes are battery operated and so energy efficient routing should be provided which increases the network life time. The existing routing mechanisms do not consider both hop count and energy of nodes for data transmission. In this paper we propose a routing mechanism where data transfer from source to destination is based on the minimum hop count and residual energy of mobile nodes. The proposed RPAR protocol shows better performance when compared to existing Energy power aware routingÂ  protocol .The analysis is carried out by using network simulator (NS-2), the simulation results shows that the proposed routing mechanism provides energy efficient and reliableÂ  routing in ad hoc networks.